Public awareness level and occurrence of pharmaceutical residues in drinking water with potential health risk in Kajang, Malaysia - Mohd Nasir, Fauzan Adzima (2020)
The presence of pharmaceutical residues in drinking water has been a subject of concern and received growing attention from environmental and health agencies worldwide. This is because pharmaceutical residues can pose negative ecotoxicological risks from a long-term exposure. In addition, the most used conventional drinking water treatment technology is ineffective for complete removal of these pollutants. Currently there is rising on global spending for medicine however the public awareness level on its disposal practice is less explored in Malaysia. Objective: To study the public awareness level on drinking water quality, occurrence of pharmaceutical residues in drinking water and potential human health risks. Methodology: The study was conducted in selected residential areas throughout Kajang. A set of modified questionnaire was administered to the respondents to assess the public awareness level and drinking water sample was taken to analyse the occurrence of pharmaceutical residues. The drinking water samples were analysed using enzyme-linked immunosorbent assay (ELISA) and the potential human health risk were calculated. Statistical analysis involved in this study were descriptive and Spearman’s rho analysis. Spearman’s rho was to investigate the correlation between knowledge, attitude and practice variables for drinking water quality and pharmaceutical residues in drinking water. Results: In general, the Kajang population posed poor knowledge for drinking water quality (71.91%) and pharmaceutical residues in drinking water (78.65%), less positive attitude for drinking water quality (88.76%) and pharmaceutical residues in drinking water (94.38%) and poor practice for drinking water quality (58.43%) and pharmaceutical residues in drinking water (69.66%). There was a moderate positive correlation between attitude score for pharmaceutical residues in drinking water and practice score for pharmaceutical residues in drinking water (r =0.541, p=0.000). All the selected pharmaceuticals were presence in drinking water samples from 0.001 to 0.667 ng/L. The highest concentration was denoted for ciprofloxacin (0.667 ng/L) while amoxicillin (0.001 ng/L) was the lowest. Nevertheless, these reported concentrations were found to be lower than studies conducted elsewhere. Besides, findings showed no adverse human health risk effect (RQ<1) from the pharmaceutical residues exposure via drinking water. Conclusion: This study has contributed to the extension of sparse information on public awareness level towards drinking water quality and pharmaceutical residues in drinking water in Malaysia, particularly for Kajang population. In addition, output of this study has provided information to fulfil the knowledge gap in pharmaceutical residues occurrence in drinking water and the potential human health risk. Besides, findings from this study can provide guideline to decision makers and authorities to improve current existing drinking water risk management and regulations related with emerging pollutants in Malaysia.